Enhancing treatment and geotechnical stability of oil sands fine tailings using thermo‐sensitive poly(n‐isopropyl acrylamide). (20th August 2015) - Li, Haihong; Zhou, Joe; Chow, Ross; Adegoroye, Adebukola; Najafi, Aref Seyyed
<x xml:space="preserve">Abstract</x> A thermo‐sensitive polymer, poly(n‐isopropyl acrylamide) (PNIPAM), was tested in the dewatering (settling, consolidation, and geotechnical stability of shear strength via vane testing) of oil sands fine tailings. The tested samples included <10 and <2 μm ("minus 10" and "minus 2") size fractions of oil sands mature fine tailings (MFT), and hydrocyclone overflow of fresh oil sands tailings. The performance of PNIPAM was compared with a selected commercial flocculant, a 30 % anionic high molecular weight polyacrylamide (PAM). Test results showed that PNIPAM worked better than PAM in fine solids flocculation, supernatant clarity, sediment consolidation, and geotechnical properties. The superiority of PNIPAM was attributed to its unique features of structural changes with temperature and the combined actions of hydrogen bonding and hydrophobic interaction of PNIPAM with the fine solid particles.